Medium, mediation and meaning: museum architecture as spatial storytelling -- a case study of the Ionic frieze in two Parthenon galleries - Lu, Fangqing (2012)
In order to convey the meanings contained within artefacts, museums commonly communicate with the general public primarily through the mediation of an audiovisual interpretative framework. In addition to audiovisual mediation, this thesis demonstrates the idea that museum architecture itself can make a significant contribution to various meanings communicated by artefacts. Drawn from a comparative case-study of the detailed interpretive frameworks of two museums, the thesis investigates the extent to which museum architecture itself should be considered as a medium of spatial-storytelling, providing a rich sensory context for the process of mediation and interpretation. This idea contributes towards a more meaningful embodied experience to the general public in order to support the process of ‘self-learning’, as well as passing on intangible culture through both tangible and intangible media. Through an initial survey and conceptual mapping of 130 museums around the world, two examples were selected effectively that offered a unique opportunity for comparative study as they are effectively exhibiting the ‘same’ material in different ways - the Ionic Frieze at the Parthenon Galleries in the British Museum and the recently opened New Acropolis Museum in Athens. Besides this survey of museums, other research methods included a literature review, interviews architectural analysis and observation of visitor behaviour, as the key data collection tools employed in this research, in order to evaluate the effectiveness of museum architecture as a medium. The thesis concludes that museum architecture offers an engaging environment for communicating meanings through ‘self-learning’, not only in terms of audiovisual techniques, but also through a careful organised embodied experience of an entire space. Moreover, museum architecture provides the artefacts a meaningful physical context in which they can ‘speak’. Culture, as an intangible medium, is recorded in the tangible media of artefacts, and buildings, while also being carried forward into an unknown future.